2018
DOI: 10.1272/jnms.jnms.2018_85-47
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer with Sarcoidosis in Spontaneous Remission: A Case Report

Abstract: A 69-year-old woman was diagnosed with sarcoidosis, which was not treated with corticosteroid therapy. Her levels of angiotensin converting enzyme decreased significantly over 4 years and a mass lesion was detected near the lower part of her left main bronchus, and diagnosed as small cell lung cancer (SCLC). Treatment of the SCLC with a series of chemotherapeutic agents produced excellent results. The pulmonary sarcoidosis did not show any deterioration despite the frequent use of amrubicin, which is known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The persistent inflammation and abnormalities in cell-mediated immunity could be a factor in triggering cancer development. 4 In this case, sarcoidosis and hilar/mediastinal lymphadenopathy were triggered by a drug with subsequent development of concurrent sarcoidosis recurrence and lung cancer in the same patient. The association between sarcoidosis and lung cancer is rare, and we propose that in our case, sarcoidosis lead to the development of lung cancer; however, the other relationships are also possible.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The persistent inflammation and abnormalities in cell-mediated immunity could be a factor in triggering cancer development. 4 In this case, sarcoidosis and hilar/mediastinal lymphadenopathy were triggered by a drug with subsequent development of concurrent sarcoidosis recurrence and lung cancer in the same patient. The association between sarcoidosis and lung cancer is rare, and we propose that in our case, sarcoidosis lead to the development of lung cancer; however, the other relationships are also possible.…”
Section: Discussionmentioning
confidence: 70%
“…Some reports suggest that people with sarcoidosis are at higher risk of lung cancer. The persistent inflammation and abnormalities in cell‐mediated immunity could be a factor in triggering cancer development 4 . In this case, sarcoidosis and hilar/mediastinal lymphadenopathy were triggered by a drug with subsequent development of concurrent sarcoidosis recurrence and lung cancer in the same patient.…”
Section: Discussionmentioning
confidence: 85%
“…The PRISMA flow diagram is depicted in Figure 3 below [10]. The patient demographics of the included case reports are described in The background and highlights of the included case reports are summarized in Table 2 below [9,[11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…According to epidemiological research, sarcoidosis and neoplasms may be etiologically associated in at least 25% of patients where both are present [ 12 ]. The association between sarcoidosis and lung cancer has been studied in several studies, one of which is the study by Brincker and Wilbek, which looked at 2,544 patients and found that lung cancer was three times more common in those with sarcoidosis [ 9 ]; however, the exact relationship between sarcoidosis and lung cancer remains unknown [ 15 ]. The reasons for this association were postulated in 1963 by the Sakula study, where three possibilities were pointed out: (1) sarcoidosis precedes lung cancer and is somehow connected to, and may even potentially trigger, the malignant transformation due to the postinflammatory scar tissue; (2) sarcoidosis may develop as a consequence of lung cancer; and (3) the onset of sarcoidosis precedes the onset of lung cancer, and the incidence of lung cancer and sarcoidosis is absolutely coincidental [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation